Positive Influences of Social Support on Sense of Community, Life Satisfaction and the Health of Immigrants in Spain - Hombrados-Mendieta, Isabel; Millán-Franco, Mario; Gómez-Jacinto, Luis; Gonzalez-Castro, Felipe; Martos-Méndez, María José; García-Cid, Alba (Frontiers in Psychology, 2019)
The main objective of this study was to investigate the association of social support and the sense of community with satisfaction with life and immigrant health. We propose a model in which perceived social support from close sources (family and friends), as mediated by sense of community and life satisfaction, would be positively associated with mental and physical health. Limited evidence exists from multivariate models that concurrently examine the association of both factors with satisfaction with life and health-related outcomes. We investigate the hypothesized asociation in a structural equations model (SEM) analysis. The participants consisted of 1131 immigrants (49% men and 51% women) (age 18-70, M = 33). The study was conducted in Malaga (Spain). Cross-sectional data were collected using a random-route sampling and survey methodology.In this model, greater social support from native friends was associated with a greater sense of community. Social support from family and native friends was associated with greater satisfaction with life. Also, a greater sense of community was associated with greater satisfaction with life. No association was found between sense of community and mental health symptoms, whereas, greater satisfaction with life was associated with fewer mental health and illness symptoms. These results suggest that among immigrants, support networks involving family and native friends, and integration into the community are important influences for immigrants to achieve life satisfaction. These results are widely applicable and have implications that are relevant to the design of health promotion interventions.